2012
DOI: 10.1159/000343044
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds and Interaction between Aminoglycosides and Natural Products of <b><i>Lygodium venustum </i></b>SW against Multiresistant Bacteria

Abstract: Background: The aim of this work was to evaluate the interactions between aminoglycosides and the ethyl-acetate fraction of the fern Lygodium venustum SW (EAFLV) Methods: The ethyl-acetate fraction was obtained from the ethanol extract of L. venustum and was assayed via the checkerboard method associated with aminoglycosides against two bacterial strains multiresistant to antibiotics. Results: The antibiotic activity of all drugs, when associated with the ethyl-acetate fraction, was enhanced in an additive man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The extracts' overall activity was moderate and correlated with their total phenol content, which was also moderate. Morais-Braga et al (2012a) utilized the DPPH assay to study the antioxidant capacity of the hexane, chloroform, ethyl acetate and methanolic fractions of P. calomelanos, revealing that the ethanolic extract and methanolic fraction showed the best results, with IC 50 values of 43.4 and 123.57 μg/mL, respectively. The activity was attributed to presence of polar compounds in the extracts such as phenolic acids and flavonoids, which have known antioxidant activity.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The extracts' overall activity was moderate and correlated with their total phenol content, which was also moderate. Morais-Braga et al (2012a) utilized the DPPH assay to study the antioxidant capacity of the hexane, chloroform, ethyl acetate and methanolic fractions of P. calomelanos, revealing that the ethanolic extract and methanolic fraction showed the best results, with IC 50 values of 43.4 and 123.57 μg/mL, respectively. The activity was attributed to presence of polar compounds in the extracts such as phenolic acids and flavonoids, which have known antioxidant activity.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Methanolic and aqueous extracts of L. venustum achieved less than 50% inhibition in all tested cases, indicating that the plant has only weak inhibitory effects on bacterial growth. Microbiological tests were also performed by Morais-Braga et al (2012a, b, 2013a, who determined the plant's MIC using the broth microdilution method and showed that extracts of the whole plant and subfractions of L. venustum had no clinically relevant effects, with a MIC ≥ 1024 µg/mL against the bacteria Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus, and the yeasts Candida albicans, Candida tropicalis, and Candida krusei. Tests of these extracts and fractions at subinhibitory concentrations (MIC/8) in combination with conventional drugs revealed no potentiation of antifungal activity.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Mahboubi et al demonstrated the antibacterial activity of the phenolic components extracted from Pleniflora flowers [ 26 ]. Moreover, many findings have indicated that phenolics exhibit broad-spectrum antibacterial activity [ 11 , 12 ]. Our results also indicate that the phenolic components extracted from walnut shell show antibacterial activity against A. ferrooxidans .…”
Section: Resultsmentioning
confidence: 99%
“…The major advantage of this technology over conventional methods includes its low cost as well as its high efficiency, the possibility of metal recovery, and the broad range of operational conditions. Moreover, some types of agricultural residue inhibit bacterial growth [ 11 , 12 ]. Walnut shell not only contains antibacterial substances, but can also absorb heavy metal ions such as Ni and Mn [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%